Respuesta :
Answer:
[tex]21y^{2} +4y-1[/tex]
Step-by-step explanation:
Hello!
[tex](12y^{2} +17y-4)+(9y^{2} -13y+3)[/tex]
For this, we can combine like terms
[tex]12y^{2} +9y^{2}=21y^{2}[/tex]
17y - 13y = 4y
-4 + 3 = -1
Combine the answers and we get
[tex]21y^{2} +4y-1[/tex]
Hope this Helps!
Answer:
21y² + 4y -1
Step-by-step explanation:
(12y² + 17y - 4) + (9y² - 13y + 3) ---- remove parentheses
= 12y² + 17y - 4y + 9y² - 13y + 3
= 12y² + 9y² + 17y - 13y - 4 + 3 -----grouped like terms
= 21y² + 17y - 13y - 4 + 3
= 21y² + 4y - 4 + 3
= 21y² + 4y - 1